A novel transforming growth factor beta‐induced long noncoding RNA promotes an inflammatory microenvironment in human intrahepatic cholangiocarcinoma. Issue 3 (30th January 2018) - Merdrignac, Aude; Angenard, Gaëlle; Allain, Coralie; Petitjean, Kilian; Bergeat, Damien; Bellaud, Pascale; Fautrel, Allain; Turlin, Bruno; Clément, Bruno; Dooley, Steven; Sulpice, Laurent; Boudjema, Karim; et al.
Abstract : The study identifies TLINC/CASC15 as a novel TGFβ‐induced long non‐coding RNA up‐regulated in human intrahepatic cholangiocarcinoma. Several isoforms of TLINC were identified, including a long‐isoform associated with migration in vitro and with an inflammatory microenvironment in vivo, as well as circular isoforms, which may represent promising tumor biomarkers. Abstract : Intrahepatic cholangiocarcinoma (iCCA) is a deadly liver primary cancer associated with poor prognosis and limited therapeutic opportunities. Active transforming growth factor beta (TGFβ) signaling is a hallmark of the iCCA microenvironment. However, the impact of TGFβ on the transcriptome of iCCA tumor cells has been poorly investigated. Here, we have identified a specific TGFβ signature of genes commonly deregulated in iCCA cell lines, namely HuCCT1 and Huh28. Novel coding and noncoding TGFβ targets were identified, including a TGFβ‐induced long noncoding RNA (TLINC), formerly known as cancer susceptibility candidate 15 (CASC15). TLINC is a general target induced by TGFβ in hepatic and nonhepatic cell types. In iCCA cell lines, the expression of a long and short TLINC isoform was associated with an epithelial or mesenchymal phenotype, respectively. Both isoforms were detected in the nucleus and cytoplasm. The long isoform of TLINC was associated with a migratory phenotype in iCCA cell lines and with the induction of proinflammatory cytokines, including interleukin 8, both in vitro and in resected human iCCA. TLINC was also identified as a tumor marker expressed in both epithelial and stroma cells. In nontumor livers, TLINC was only expressed in specific portal areas with signs of ductular reaction and inflammation. Finally, we provide experimental evidence of circular isoforms of TLINC, both in iCCA cells treated with TGFβ and in resected human iCCA. Conclusion : We identify a novel TGFβ‐induced long noncoding RNA up‐regulated in human iCCA and associated with an inflammatory microenvironment. ( Hepatology Communications 2018;2:254‐269)